2008
DOI: 10.1529/biophysj.107.115477
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemical and Structural Anisotropy on the Electrophoretic Mobility of Spherical Soft Multilayer Particles: The Case of Bacteriophage MS2

Abstract: We report a theoretical investigation of the electrohydrodynamic properties of spherical soft particles composed of permeable concentric layers that differ in thickness, soft material density, chemical composition, and flow penetration degree. Starting from a recent numerical scheme developed for the computation of the direct-current electrophoretic mobility (mu) of diffuse soft bioparticles, the dependence of mu on the electrolyte concentration and solution pH is evaluated taking the known three-layered struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
228
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(249 citation statements)
references
References 94 publications
19
228
2
Order By: Relevance
“…For MS2 phage, the measured IEP value (ϳ3.5 to 3.9) is lower than that expected if considering the capsid (IEP of Ͼ8) (10,15,19) only. As detailed previously (10), the dependence of electrophoretic mobility of MS2 phage on solution ionic strength is typical of that classically encountered for soft (i.e., permeable) particles.…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…For MS2 phage, the measured IEP value (ϳ3.5 to 3.9) is lower than that expected if considering the capsid (IEP of Ͼ8) (10,15,19) only. As detailed previously (10), the dependence of electrophoretic mobility of MS2 phage on solution ionic strength is typical of that classically encountered for soft (i.e., permeable) particles.…”
contrasting
confidence: 59%
“…The IEP value of viruses, which are paradigms of permeable (soft) multilayered biocells (10), is significantly impacted by their permeability to external flow (electroosmotic flow developed during the migration of the particles under the action of the externally applied field), as theoretically and experimentally demonstrated by Langlet et al (10). The IEP of soft multilayered particles is generally a complex, ionic-strength-dependent signature of the intertwined electrostatic and permeability properties of the whole particle.…”
mentioning
confidence: 97%
“…The adsorption of viral particles to a membrane is due to electrostatic interactions but depend on both the environmental characteristics and surface properties of the virus (20). Studies showed that charges of influenza viruses above their isoelectric point, which was approximately 5 (11, 23), were negative.…”
Section: Discussionmentioning
confidence: 99%
“…In the diffuse soft particle electrokinetic theory (DSPE) given by J. F. Duval [11,12], the gradual decay of the electrodynamic properties of the soft layer inside and outside the particle was considered. The extensions of the DSPE theory to multilayer soft particles have been recently done [13,14]. The inhomogeneous distribution of the charged polymer segments is demonstrated to substantially affect the overall electrokinetic response, especially in the low electrolyte concentration regime.…”
Section: Introductionmentioning
confidence: 99%